Inflammation during Lung Cancer Progression and Ethyl Pyruvate Treatment Observed by Pulmonary Functional Hyperpolarized 129Xe MRI in Mice. (29th June 2021) - Kimura, Atsuomi; Utsumi, Seiya; Shimokawa, Akihiro; Nishimori, Renya; Stewart, Neil J.; Kamada, Yoshihiro; Imai, Hirohiko; Fujiwara, Hideaki
Abstract : This study aimed to assess the suitability of hyperpolarized 129 Xe (HPXe) MRI for noninvasive longitudinal evaluation of pulmonary function in preclinical lung cancer models. A mouse model of lung cancer (LC) was induced in 5 mice by intraperitoneal injection of urethane, while a negative-control (NC) mice ( N  = 5) was prepared by injection of saline solution. Longitudinal HPXe MRI was performed over a 5-month period to monitor lung ventilation and gas exchange. The treatment efficacy of ethyl pyruvate (EP), an anti-inflammatory drug, to the mouse LC model was monitored using HPXe MRI by commencing administration of EP pre (early-phase) and 1-month post (late-phase) injection of urethane ( N  = 5 mice for each group). Gas-exchange function in LC mice was significantly reduced at 1-month after urethane injection compared with NC mice administered with saline (P < 0.01 ). Thereafter, it remained consistently lower than that of the NC group for the full 5-month measurement period. In contrast, the ventilation function of the LC model mice was not significantly different to that of the NC mice. Histological analysis revealed alveolar epithelial hyperplasia in LC mice alveoli at 1 month after urethane injection, and adenoma was confirmed 3 months after the injection. The early- and late-phase EP interventions were found to improve HPXe MRI metrics (reduced at 1 month postinjection of urethane) and significantly inhibit tumor growth. These results suggest that HPXe MRI gas-exchange metrics can be used to quantitatively assess changes in the precancerous lesion microenvironment and to evaluate therapeutic efficacy in cancer. Thus, HPXe MRI can be utilized to noninvasively monitor pulmonary pathology during LC progression and can visualize functional changes during therapy.